Silver-Based Plasmonic Grating with PDMS Microchannel for Biological Sensors - Pongsak Sarapukdee; Dirk Schulz; Stefan Palzer (Proceedings)
The label-free approach streamlines sample analysis by eliminating the need for fluorescent markers or labels, thus improving accuracy and speed. This contribution explores the potential of silver-based plasmonic gratings as central building blocks for developing biological sensors using label-free detection techniques. It presents the design, fabrication, and optimization of plasmonic gratings, including showcasing their application in biological molecule detection.